Prevalence and predictors of overweight and obesity among women in the Gaza strip-Palestine: a cross-sectional study - Rima Rafiq El Kishawi; Kah Leng Soo; Yehia Awad Abed; Wan Abdul Manan Wan Muda (BMC, 2020)
Abstract Background The prevalence of overweight and obesity among women of childbearing age is considered a public health concern. Few studies have been conducted in the Gaza Strip to determine the magnitude of overweight and obesity. This study aimed to determine the prevalence of overweight and obesity along with their associated factors among women in the Gaza Strip. Methods A cross-sectional study was conducted to recruit a total of 357 mothers aged 18-50 years. Interviews were carried out among mothers to collect sociodemographic information, nutritional information, and physical activity. Anthropometric measurements [height, weight and waist circumference (WC)] were conducted with the mothers. Body Mass Index (BMI) was computed to determine the prevalence of overweight and obesity. Multinomial logistic regression was used to examine the associated factors of overweight and obesity. Results The combined prevalence of overweight and obesity among mothers was (64.1%). The results of multinomial logistic regression showed the risk of overweight and obesity increased with age, the highest risk being in mothers aged > 33.0 years (OR = 2.7, 95% CI: (1.06,6.86)), and (OR = 5.72, 95% CI: (2.07,15.78)), respectively, compared to mothers aged < 33.0 years. Moreover, mothers with medium and high educational levels had a slightly higher risk of obesity (OR = 0.31, 95% CI: (0.15,0.64)), and (OR = 0.32, 95% CI: (0.12,0.82)) respectively than mothers with low educational level. Household income was positively associated with overweight and obesity. Mothers exposed to higher monthly income were more likely to be overweight or obese (OR = 2.64, 95% CI: (1.20, 5.83)), and (OR = 3.06, 95% CI: (1.28,7.29)), respectively. Nutrition knowledge was significantly associated with a high prevalence of obesity (OR = 1.20, 95% CI: (1.03,1.38)). Conclusions This study showed a higher prevalence of overweight and obesity among Palestinian women than previous studies. Age, educational level, monthly income, and nutrition knowledge were associated with the prevalence of overweight and obesity, compared to other variables that were not associated with overweight and obesity such as location, work status, physical activity, and sitting hours. Urgent action is needed to tackle overweight and obesity among women. Effective intervention is required to increase nutrition knowledge among women to improve their eating behaviors.